Mediation of Short and Longer Term Effects of an Intervention Program to Enhance Resilience in Immigrants from Mainland China to Hong Kong - Yu, Nancy X.; Lam, T. H.; Liu, Iris K. F.; Stewart, Sunita M. (Frontiers in Psychology, 2015)
Few clinical trials report on the active intervention components that result in outcome changes, although this is relevant to further improving efficacy and adapting effective programs to other populations. This paper presents follow-up analyses of a randomized controlled trial to enhance adaptation by increasing knowledge and personal resilience in two separate brief interventions with immigrants from Mainland China to Hong Kong (Yu et al., 2014b). The present paper extends our previous one by reporting on the longer term effect of the interventions on personal resilience, and examining whether the Resilience intervention worked as designed to enhance personal resilience. The four-session intervention targeted at self-efficacy, positive thinking, altruism, and goal setting. In this randomized controlled trial, 220 immigrants were randomly allocated to three arms: Resilience, Information (an active control arm), and Control arms. Participants completed measures of the four active components (self-efficacy, positive thinking, altruism, and goal setting) at baseline and immediately after the intervention. Personal resilience was assessed at baseline, post-intervention, and three- and six-month follow-ups. The results showed that the Resilience arm had greater increases in the four active components post-intervention. Changes in each of the four active components at the post-intervention assessment mediated enhanced personal resilience at the three-month follow-up in the Resilience arm. Changes in self-efficacy and goal setting showed the largest effect size, and altruism showed the smallest. The arm effects of the Resilience intervention on enhanced personal resilience at the six-month follow-up were mediated by increases of personal resilience post-intervention (Resilience versus Control) and at the three-month follow-up (Resilience versus Information). These findings showed that these four active components were all mediators in this Resilience intervention. Our results of the effects of short term increases in personal resilience on longer term increase in personal resilience in some models suggest how changes in intervention outcomes might persist over time.